ASSESSMENT OF NAUSEA AND VOMITING STATUS IN PATIENTS AFTER GASTROINTESTINAL CANCER SURGERY DURING THE RECOVERY PERIOD (Vietnam Journal of Community Medicine, 2026)
Objective: To assess postoperative nausea and vomiting (PONV) among patients undergoing surgery for gastrointestinal cancer during the recovery period at the Intensive Care Unit, K Hospital.Subjects and Methods: A descriptive cross-sectional study was conducted among 110 patients who underwent surgery for gastrointestinal cancer at the Intensive Care Unit, Tan Trieu Campus, K Hospital. Data were collected from medical records, patient interviews, and direct observation using a predesigned data collection tool. The risk of PONV was assessed using the Apfel score, while the severity of PONV was assessed using the Klockgether-Radle scale.Results: Most patients had an Apfel score of 0 (56.4%), while 4.5% had an Apfel score of 4. Prophylactic medication for PONV was administered to 97.3% of patients. The overall incidence of PONV during the observation period was 36.4%, of whom 62.5% were female. PONV was predominantly mild (Klockgether-Radle score of 1–2) and occurred mainly during the early period after extubation; 72.5% of vomiting episodes occurred within the first 30 minutes. Among the 40 patients who developed PONV, 11 required rescue antiemetic treatment. The incidence of PONV tended to increase with higher Apfel risk scores. In the analysis of associated factors, age younger than 50 years and the presence of a gastric tube were associated with PONV.Conclusion: The incidence of PONV during the postoperative recovery period was 36.4%, with most cases being mild and occurring during the early period after extubation. PONV was more common among female patients. A higher Apfel risk score, age younger than 50 years, and the presence of a gastric tube were associated with the occurrence of PONV.
Keywords: postoperative nausea vomiting (PONV), Apfel score, Klockgether-radle score.